Polydopamine-Based "Four-in-One" Versatile Nanoplatforms for Targeted Dual Chemo and Photothermal Synergistic Cancer Therapy - Gan Liu; Nansha Gao; Yun Zhou; Junpeng Nie; Wei Cheng; Miaomiao Luo; Lin Mei; Xiaowei Zeng; Wenbin Deng (MDPI AG, 2019)
The development of versatile nanoscale drug delivery systems that integrate with multiple therapeutic agents or methods and improve the efficacy of cancer therapy is urgently required. To satisfy this demand, polydopamine (PDA)-modified polymeric nanoplatforms were constructed for the dual loading of chemotherapeutic drugs. The hydrophobic anticancer drug docetaxel (DTX) was loaded into the polymeric nanoparticles (NPs) which were fabricated from the star-shaped copolymer CA-PLGA. Then DTX-loaded NPs were coated with PDA, followed by conjugation of polyelethyl glycol (PEG)-modified targeting ligand aptamer AS1411(Apt) and adsorption of the hydrophilic anticancer drug doxorubicin (DOX). This “four-in-one” nanoplatform, referred to as DTX/NPs@PDA/DOX-PEG-Apt, demonstrated high near-infrared photothermal conversion efficiency and exhibited pH and thermo-responsive drug release behavior. Furthermore, it was able to specifically target MCF-7 human breast carcinoma cells and provide synergistic chemo-photothermal therapy to further improve the anticancer effect both in vitro and in vivo, providing a novel promising strategy for cancer therapy.